Syndemic conditions and medication adherence in older men living with HIV who have sex with men. Issue 12 (1st December 2020) - Zepf, R.; Greene, M.; Hessol, N. A.; Johnson, M. O.; Santos, G. M.; John, M. D.; Dawson-Rose, C.
ABSTRACT: For people living with HIV, lack of adherence to antiretroviral therapy (ART) is a serious problem and frequently results in HIV disease progression. Reasons for non-adherence include concomitant psychosocial health conditions – also known as syndemic conditions – such symptoms of depression or posttraumatic stress disorder (PTSD), past physical or sexual abuse, intimate partner violence (IPV), stimulant use, and binge drinking. The aim of this study was to investigate the association between syndemic conditions and medication adherence. The sample included 281 older men living with HIV who have sex with men (MSM). The study period was December 2012–July 2016. We observed the following syndemic conditions significantly decreased medication adherence: symptoms of depression ( p =  .008), PTSD ( p =  .002), and stimulant use ( p <  .0001). Past physical or sexual abuse, IPV, and binge drinking were not significantly associated with decreased medication adherence. The findings suggest that syndemic conditions may impact medication adherence in older MSM living with HIV.